Results in strongly minihedral cone and scalar weighted cone metric spaces and applications - Tomar, Anita; Joshi, Meena (Annales Mathematicae Silesianae, 2021)
The convergence of sequences and non-unique fixed points are established in M-orbitally complete cone metric spaces over the strongly minihedral cone, and scalar weighted cone assuming the cone to be strongly minihedral. Appropriate examples and applications validate the established theory. Further, we provide one more answer to the question of the existence of the contractive condition in Cone metric spaces so that the fixed point is at the point of discontinuity of a map. Also, we provide a negative answer to a natural question of whether the contractive conditions in the obtained results can be replaced by its metric versions.